Perceptions of audiovisual media in vocabulary acquisition among English learners: benefits and challenges - Thi, Xuan Hong Nguyen; Nguyen, Thanh Thai (International Journal of Evaluation and Research in Education (IJERE), 2025)
Learning vocabulary through English audiovisual materials has long been a popular method among students. With the advancement of digital technology, this approach has gained even more attraction, leading to a growing number of studies that have investigated its effectiveness. However, there is a notable scarcity of research addressing the challenges that students face; therefore, the current study aims to explore students’ perspectives on the challenges along with the benefits of using audiovisual media as tools for learning vocabulary. This study was done through a quantitative approach using a questionnaire that included both open-ended and closed-ended questions. With the participation of 132 senior English-major students at Thu Dau Mot University in Vietnam, the study collected 117 valid questionnaires that provided valid data for analysis. Through descriptive statistics, the results reveal the improvements in pronunciation and listening skills, enhanced understanding of slang and idiomatic expressions, and increased exposure to the natural use of the target language. However, the findings also reveal that this method poses challenges for students, including misunderstandings stemming from the use of formal or informal language and an over-reliance on audiovisual media. Therefore, the study emphasizes the need for structured guidance to foster language learning outcomes.